Traumatic Diaphragmatic Rupture, Incidence, Presentation, and Outcome - Gialan, Waleed Mohammed; Obadiel, Yasser Abdurabu; Mohammed, Abdulrazzak Abdullah (Journal of medical and pharmaceutical sciences, 2021)
Objective: The aim of this prospective study is to highlight the incidence of a traumatic diaphragmatic rupture occurring in thoraco-abdominal penetrating or blunt trauma, and discuss their presentation and outcomeMethods: We performed a prospective study, between 1st January 2017 to 30th June 2020 at the Department of General Surgery of the Al-Thawra Modern General Hospital, and 48-Modrn hospital -Sana'a city -Yemen. We included all the patients who were diagnosed and admitted with traumatic diaphragmatic rupture during the study period. Data included demographics, mechanism of injury, associated injuries, time of presentation post- trauma, length of hospital stay and ICU, ventilator days, management, postoperative complication, and outcomes. The variables were analyzed and compared for patients.Result: A total of 38 patients had traumatic diaphragmatic injury of (1843) thoracoabdominal trauma (2.1%)(855 blunt trauma & 988 penetrating trauma), 31 patients (81.6%) have sustained penetrating trauma, while only 7 patients (18.4%) have blunt trauma. There were 33 male patients (86.8%) and 5 female patients (13.2%) with a mean age of 25 years (range 3–52 years), the location of rupture was 30 patients (78.9%) on the left-sided, and 8 patients (21.1%) on right-sided, 4 patients presented early with a diaphragmatic hernia, and 5 patient presented late with diaphragmatic hernia. Associated injuries were presented in 36 patients (94.7%). The diagnosis was preoperatively established in (36.8%), and intraoperative (63.2%). The diaphragmatic rupture was repaired with interrupted nonabsorbable sutures. Postoperative complications were observed in 23 patients (60.5%). Mortality was observed in 4 patients (10.5%). The outcome affected by associated injuries hemo/pneumothorax, rib fractures/lung contusion, hollow viscous injury, post-operative complication, time of presentation post- trauma, and hemodynamically state before admission.Conclusion: Traumatic diaphragmatic rupture, usually masked by multiple associated injuries which aggravate the condition of patients and are responsible for morbidity and mortality. The left-sided is involved more than the right-sided.
Keywords: Traumatic diaphragmatic rupture; Blunt; penetrating; thoracoabdominal